Factors affecting hemoglobin levels of patients with end-stage kidney disease in the maintenance phase: A prospective observational study - Maryadi, Maryadi; Khudazi Aulawi; Uki Noviana (Journal of Associated Medical Sciences, 2025)
Background: Patients with end-stage kidney disease (ESKD) undergoing hemodialysis almost invariably develop anemia, which can significantly impair their quality of life. It is uncommon to find patients with consistently normal hemoglobin (Hb) levels; therefore, identifying the contributing factors is essential. Objectives: This study aimed to identify factors affecting Hb levels in ESKD patients during maintenance phase. Materials and methods: This prospective observational study was conducted at a regional hospital in Yogyakarta. The Hb cutoff point of 10 g/dL was used as the minimum standard for the maintenance phase, based on the Dialysis Consensus of the Indonesian Nephrology Association. The study included ESKD patients aged ≥18 years undergoing hemodialysis. The initial sample comprised 76 patients (38 with Hb >10 gm/dL and 38 with Hb ≤10 gm/dL); however, 65 patients were included in the final analysis after 11 were excluded due to dropout. Samples were matched based on age, sex, duration of hemodialysis, and comorbidities. Data were collected using patient medical record observation sheets, food record sheets, and the brief illness perception questionnaire (B-IPQ). Statistical analyses were performed using chi-square and logistic regression with a backward elimination method. Results: A total of 65 participants were analyzed (33 patients with Hb >10 and 32 patients with Hb ≤10). Factors that showed significant associations with Hb levels were erythropoietin-stimulating agent (ESA) therapy odds ratio (OR)=7.162, 95% confidence interval [CI]=2.046-25.071, p=0.002), duration of hemodialysis (OR=4.909, 95% CI=1.299-18.551, p=0.019), and vitamin B12 intake (OR=4.238, 95% CI=1.183-15.176, p=0.027). Conclusion: Erythropoietin stimulating agent therapy, duration of hemodialysis, and vitamin B12 intake were identified as factors influencing the improvement of Hb levels in patients with ESKD. Educational interventions are needed to enhance patients’ understanding of the importance of maintaining balanced nutritional intake and adhering to optimal hemodialysis duration.